Thoracic tumours essentials for clinicians - Stahel, Rolf A; Peters, Solange; Garassino, Marina (ESMO Press, 2019)
The publications focuses on various aspects of thoracic tumours. Intended for professional public.
Keywords: onkologie; Medical Oncology; nádory hrudníku; lékařská onkologie; Thoracic Neoplasms